The Practice of Enterprise Modeling 8th IFIP WG 8.1. Working Conference, PoEM 2015, Valencia, Spain, November 10-12, 2015, Proceedings - Ralyté, Jolita; España, Sergio; Pastor, Óscar (Lecture Notes in Business Information Processing, 2015)
This volume constitutes the proceedings of the 8th IFIP WG 8.1 Conference on the Practice of Enterprise Modeling held in November 2015 in Valencia, Spain. The PoEM conference series started in 2008 and aims to provide a forum sharing knowledge and experiences between the academic community and practitioners from industry and the public sector. The 23 short papers accepted were carefully reviewed and selected from 72 submissions and are organized in eight sections on Evolving Enterprises, Securing Enterprises, Making Empirical Studies, Investigating Enterprise Methods, Acquiring User Information, Managing Risks and Threats, Engineering Methods, and Making Decisions in Enterprises. .